4, 8-Bis(thienyl)-benzo[1, 2-b:4, 5-b′]dithiophene based A-π-D-π-A typed conjugated small molecules with mono-thiophene as the π-bridge: Synthesis, properties and photovoltaic performance. (September 2015) - Yin, Ni; Wang, Lilei; Ma, Yuchao; Lin, Yi; Wu, Jianchang; Luo, Qun; Yang, Hai-Bo; Ma, Chang-Qi; Zhao, Xin
Abstract: Two conjugated A-π-D-π-A type small molecules having a 4, 8-bis(thienyl)-benzo[1, 2- b :4, 5- b ′]dithiophene (TBDT) unit as the donor part, a mono-thiophene as the π-conjugation bridge, and 2-cyano-3-octyloxy-3-oxo-1-propenyl (COOP) or dicyanovinyl (DCV) as the terminal acceptor unit were synthesized and investigated. Both compounds showed broad absorption band over 400–600 nm and similar HOMO/LUMO energy levels. However, these two compounds showed a big difference in photovoltaic performance. The DCV-1T-TBDT :PC61 BM based solar cell exhibited an open circuit voltage ( V OC ) of 0.93 V, a short circuit current ( J SC ) of 8.54 mA cm −2, a fill factor (FF) of 0.56, and an overall power conversion efficiency (PCE) of 4.48%, whereas the COOP-1T-TBDT :PC61 BM based solar cell showed a V OC of 1.04 V, a J SC of 2.28 mA cm −2, an FF of 0.29, and a PCE of 0.69. Furthermore, DCV-1T-TBDT showed minor thickness-dependent PCE behavior in PV device, which is beneficial for printing processing. Graphical abstract: Highlights: Two BDT-based A-π-D-π-A type small molecules with monothiophene as the π-conjugated bridge were synthesized. Devices based on these two compounds showed high V OC of 0.93–1.04 V. The DCV-1T-TBDT :PC61 BM based solar cell gave an overall power conversion efficiency (PCE) of 4.48%. DCV-1T-TBDT showed minor layer thickness-dependence.